The X Process: Anti-Psychiatry and Its Hopes. - White, Rob (New England Review (10531297), 2017)
The article focuses on psychiatrist R.D. Laing who started his medical career at Gartenavel Hospital in Glasgow, Scotland as an enthusiastic innovator and mentions how he said that it was proof that traditional psychiatriy could be reformed. Topics inlcude how anti-psychiatry was born out of anger at the mistreatment of patients who were labeled crazy, Liang's interested in the self's solitariness and vulnerability and his book "Psychiatry & Anti-Psychiatry."